Improving English Writing Skills through the Application of Audiovisual Media at Senior High School - Amatollah Amatollah; Suparman Suparman; Pratiwi Sakti (Universitas Pahlawan Tuanku Tambusai, 2022)
The author found that there was still a lack of mastery and interest of students in writing English sentences at SMAN 3 Sumbawa Besar. This study aims to explain strategies for using audiovisual media as well as analyze the results of improving English writing skills in the use of audiovisual media. This type of research is descriptive quantitative with the data collection techniques used are observation, English writing skills test and documentation and the analysis technique used is the paired sample t-test. Based on the results of the descriptive statistical analysis test, the average score of pretest and posttest English writing was obtained by students in the control class of 50.88 and 59.56 experienced an increase in scores in the experimental class of 58.68 and 74.85, meaning that there was an increase in English writing skills after the use of audiovisual media. From the analysis of the pretest-postest paired t-test, a result of -35.098 with a sig value was obtained. hitug (2 tailed) 0.000 is smaller than the ttabel 0.05. It was concluded that there was a difference between the pretest and postest scores in the results of English writing skills before using audiovisual media and after using audiovisual media.